Materials Characterization - Pérez Campos, Ramiro; Contreras Cuevas, Antonio; Esparza Muñoz, Rodrigo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book covers novel research results for process and techniques of materials characterization for a wide range of materials. The authors provide a comprehensive overview of the aspects of structural and chemical characterization of these materials.  The articles contained in this book covers state of the art and experimental techniques commonly used in modern materials characterization. The book includes theoretical models and numerous illustrations of structural and chemical characterization properties.
Preface -- Acknowledgements -- Characterization Of Welding And Joining Of Materials -- Characterization Of Nanostructured Materials -- Characterization Of Steels Used In The Oil Industry -- Characterization Of Stainless Steels -- Characterization Of Composite Materials -- Characterization Of Materials For Medical Applications -- Characterization Of Materials For Industrial Applications -- Characterization Of Intermetallic Materials.
Keywords: Materials science; Spectroscopy; Microscopy; Characterization and Evaluation of Materials; Spectroscopy and Microscopy